SOCIODEMOGRAPHIC AND CLINICAL FACTORS ASSOCIATED WITH HAND GRIP STRENGTH AND GAIT SPEED IN LONG-LIVING ELDERLY - Maria Helena Lenardt; Clóris Regina Blanski Grden; Jacy Aurelia Vieira de Sousa; Susanne Elero Betiolli; Péricles Martim Reche; Tânia Maria Lourenço (Universidade Federal do Paraná, 2017)
Abstract Cross-sectional research to investigate the association between sociodemographic and clinical factors and the components hand grip strength and gait speed in long-living elderly. The sample included 243 long-living elderly from three primary health care services in Curitiba, Paraná, between January 2013 and September 2015. A significant association was identified between hand grip strength and sex (p=0.001), age (p=0.001), marital status (p=0.001), housing (p=0.001), falls in previous year (p=0.03), urine loss (p=0.001), use of cane (p=0.001) and walker (p=0.001). The gait speed was associated with sex (p=0.001), age (p=0.001), marital status (p=0.001), housing (p=0.001), falls in previous year (p=0.03), urine loss (p=0.001), use of cane (p=0.001) and walker (p=0.001). It is highlighted that the assessment of hand grip strength and gait speed helps to identify functional changes in long-living elderly and plays a fundamental role in the management of the physical frailty syndrome.